Borders in motion: An application related to the video game "Animal Crossing: New Horizons" - Behailu Shiferaw Benti; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2021)
In 2020, the video game Animal Crossing: New Horizons was listed among the top ten in terms of revenue. We analyze the game by relying on an interdisciplinary framework of border studies. Borders can be interpreted not only in a geographical sense but also in terms of a temporal dimension as well as a cultural dimension. We highlight how the game blurs the borders between the real and virtual world.
Keywords: 330; Border; Animal Crossing; real versus virtual world